Rational Emotive Behavior Therapy and Islamic Counseling: An Experimental Study to Reduce Students' Pornographic Behavior - Alif Al Uhair; Yuniarfa; Rian Aryanto; RA. Hari Utami Dewim; Winda Nuraisyah (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
This study aims to examine the difference in effectiveness between the three treatment groups to reduce pornographic behavior for students of SMA Negeri 3 Sumenep. This study is a quantitative research with a Quasy Experimental design, there is a control group and an experimental group. The sample uses purposive sampling , namely students who have a relatively high pornography score on the pornography scale of 22 students were divided into 3 treatment groups. The research instrument is a questionnaire that has been validated, supported by data sources, namely interviews, observations, and documentation. Data analysis used a single-path Anova, a normality test method using Shapiro-Wilk, and a homogeneity test using the Test of Homogeneity of Variances. The results of the normality test were normally distributed, which was classified as parametric, the results of the homogeneity test for all groups were homogeneous, while the results of the Anova test showed a difference in the decrease in pornographic behavior after receiving treatment compared to before treatment, the REBT group counseling treatment combined with Islamic counseling was more effective than the other two treatments. Then pornographic behavior or deviant or immoral behavior should be reduced by using effective counseling methods and techniques to solve students' problems